Mortality rate associated with diabetes: outcomes from a general practice level analysis in England using the Royal College of General Practitioners (RCGP) database indicate stability over a 15 year period - Heald, A; Stedman, M; Robinson, A; Davies, M; Livingston, M; Alshames, R; Moreno, G; Gadsby, R; Rayman, G; Gibson, M; de Lusignan, S; Whyte, M (Springer, 2022)
Introduction: Total population mortality rates have been falling and life expectancy increasing for more than 30 years. Diabetes remains a significant risk factor for premature death. Here we used the Oxford Royal College of General Practitioners Research and Surveillance Centre (RCGP RSC) practices to determine diabetes-related vs non-diabetes-related mortality rates. Methods: RCGP RSC data were provided on annual patient numbers and deaths, at practice level, for those with and without diabetes across four age groups (< 50, 50–64, 65–79, ≥ 80 years) over 15 years. Investment in diabetes control, as measured by the cost of primary care medication, was also taken from GP prescribing data. Results: We included 527 general practices. Over the period 2004–2019, there was no significant change in life years lost, which varied between 4.6 and 5.1 years over this period. The proportion of all diabetes deaths by age band was significantly higher in the 65–79 years age group for men and women with diabetes than for their non-diabetic counterparts. For the year 2019, 26.6% of deaths were of people with diabetes. Of this 26.6%, 18.5% would be expected from age group and non-diabetes status, while the other 8.1% would not have been expected—pro rata to nation, this approximates to approximately 40,000 excess deaths in people with diabetes vs the general population. Conclusion: There remains a wide variation in mortality rate of people with diabetes between general practices in UK. The mortality rate and life years lost for people with diabetes vs non-diabetes individuals have remained stable in recent years, while mortality rates for the general population have fallen. Investment in diabetes management at a local and national level is enabling us to hold the ground regarding the life-shortening consequences of having diabetes as increasing numbers of people develop T2DM at a younger age.